Analysis of Errors in Students' Mathematical Communication Skills Based on Kastolan Stages at Ban Eyoh School, Thailand - Lubis, Sri Wahyuni; Fitriani, Fitriani; Lubis , Ainun Mardiyah; Siregar , Yulia Anita; Samoh, Sakinah (UNNES JOURNAL, 2024)
Communication ability is one of the five basic abilities of mathematics. Understanding communication ability is one of the important things in building a learning design suitable for students' ability levels. This study analyzes the mathematical communication based on the Kastolan stages of ability of 6th-grade students at Ban Eyoh School in Thailand in answering fractional arithmetic story problems. Three students who took the sample in the study, S1 scored 94, S2 scored 83, and S3 scored 72, were reviewed for high, moderate, and low communication ability. Students generally have difficulties in presenting steps in writing, especially in explaining what is known and asked about stories. Kastolan stage analysis reveals various conceptual, procedural, and technical errors, including challenges in converting mixed fractions and a lack of coherence in the solution process. Recommendations include a focus on written expression, enhanced conceptual understanding and school facilities support to improve students' mathematical communication ability. By understanding the level of students' communication ability, the results of this research can become the basis for didactical research to develop appropriate learning designs. This research can also be continued with research related to constructive feedback. Kemampuan komunikasi merupakan salah satu dari 5 kemampuan dasar bermatematika. Memahami kemampuan komunikasi adalah salah satu hal penting untuk membangun desain pembelajarna yang sesaui dengan level kemampuan siswa. Penelitian kualitatif deskriptif ini menganalisis kesalahan kemampuan komunikasi matematika berdasarkan tahapan kastolan pada siswa kelas 6 di Ban Eyoh School Thailand dalam menjawab soal cerita operasi hitung pecahan. Tiga siswa yang menjadi sampel dalam penelitian, S1 dengan skor 94, S2 dengan skor 83, dan S3 dengan skor 72, ditinjau dari kemampuan komunikasi tinggi, sedang, dan rendah. Siswa umumnya menghadapi kesulitan dalam menyajikan langkah-langkah secara tertulis, terutama dalam menjelaskan hal yang diketahui dan ditanyakan pada soal cerita. Analisis tahapan kastolan menunjukkan berbagai kesalahan konseptual, prosedural, dan teknikal, termasuk kesulitan dalam mengubah pecahan campuran dan kurangnya keteraturan dalam proses penyelesaian. Rekomendasi mencakup penekanan pada aspek tertulis, peningkatan pemahaman konsep, dan dukungan fasilitas sekolah untuk meningkatkan kemampuan komunikasi matematis siswa. Dengan memahami level kemampuan komunikasi siswa, hasil riset ini dapat menjadi dasr riset didaktis untuk mengembangkan desain pembelajaran yang sesaui. Riset ini dapat juga dilanjutkan dengan riset terkait feedback yang membangun.